Análise de aulas remotas a partir da teoria do código de legitimação : a pesquisa como processo de formação continuada de professores de química - Andrade, Danielle Guimarães de (2022)
The present study sought to help chemistry teachers working in Basic Education who are in the process of continuing education, to understand and reflect on their practice based on theoretical contributions. For this, we designed the research through an investigation strategy based on metacognitive processes, seeking to recognize and understand the problems in order to try to promote possible solutions for the teaching of both. As an analytical framework that allows us to observe the organizational principles underlying the practice, we used the Theory of the Code of Legitimation (TCL) as a tool to visualize the pedagogical characteristics. The research structure was built along the lines of the Multipaper format, which allows the presentation of multiple approaches through a collection of publishable articles. In the first article, we used the methodology of educational mapping, of an exploratory nature, to understand the aspects and uses of TCL in the educational field. Then, we explored the theoretical concepts that helped in the construction of the TCL and analyzed translation devices aimed at teaching chemistry, building a new specific analysis tool for remote chemistry classes, in the second article. Finally, in the third empirical study, we analyzed remote chemistry classes of the two participating teachers, through the Theory of the Code of Legitimation and its Semantic Dimension, organized by the semantic codes of Gravity and Density, with the objective of bringing the field of research and its continuing education process, seeking to understand the relationship between pedagogical actions and the quality of student learning. The results showed that the processes of metacognition of teaching strategies from the practice of chemistry teachers allow reflections and changes, serving as feedback from the theoretical-analytical level.